Association of jumping ability and maximum strength with dive distance in swimmers - Calderbank, J. A.; Comfort, P.; McMahon, J. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The aim of the current study was to investigate the relationship between dive distance (DD) and countermovement jump (CMJ) height, track start CMJ height, countermovement broad jump (CMBJ) distance, track start broad jump distance, and isometric midthigh pull peak force and relative peak force. Methods: A total of 27 (11 female and 16 male) regional-national-international-standard swimmers (mean [SD]; age = 19.5 [5.5] y; mass = 69.3 [10.5] kg; height = 1.77 [0.09] m) performed 3 trials of a track start dive, CMJ, track start CMJ, CMBJ, track start broad jump, and isometric midthigh pull. Results: Data were separated into pooled (females and males combined), females, and males. Large to very large correlations were found between DD and all variables tested for pooled data (r = .554-.853, P < .001-.008), with DD-CMBJ displaying the highest correlation (r = .853, P < .001). CMBJ accounted for 70% of the variance in DD. Females demonstrated moderate nonsignificant correlations between DD isometric midthigh pull (r = .379, P < .125). Males demonstrated very large significant correlations between DD-CMJ (r = .761, P < .001). Conclusions: DD demonstrated strong correlations with jump performances and multijoint isometric force production in pooled data. Males showed stronger correlations than females due to being stronger and being able to perform the jumping/strength tasks to a higher standard. Enhanced jump performance and increased maximal force production may, therefore, enhance DD in swimmers.